Livestock Recovery Programme on Merapi Disruption Area - Atien Priyanti; Bambang Risdiono Prawirodiputra; Ismeth Inounu; Pius P Ketaren (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2011)
Livestock Recovery Programme on Merapi Disruption Area A series of volcano eruption of Merapi on October and November 2010 was one of the biggest eruptions since 1872 with around 275 people died, 576 people in hospital and 287.131 people were evacuated. This disaster has impacted to the threatened livestock subsector that cannot be from farmers in the rural areas, especially in the Merapi surrounding areas. The proportion of livestock to total population was 14, 39 and 21,5%, for beef cattle, dairy and buffaloes respectively. Total of cattle died were 2.907 heads and the district of Sleman suffered the highest loss in livestock deaths in which 43% of the threatened dairy population died. A various action program has been carried out to recovery, i.e. supply of concentrate and wafer plus, knock down barn innovation for dairy, along with supply of medicine and services for better life of livestock. Recommendations of medium and long terms action programme for rehabilitation and reconstruction of livestock farming include: repair on water supply, innovation of complete feed, forage rehabilitation plantation, composting management and biogas usage, knock down for dairy barn to anticipate the Merapi eruption in the future, and surveillance on the possibilities of contamination and strategic animal diseases. Rehabilitation and reconstruction effort may recover the farmer economic livelihood that has been devastated in a liable period of time. Key words: Merapi disruption, livestock recovery